The role of Islamic microfinance towards SDGs 2030 from poverty alleviation - Rusyda Afifah Ahmad; Helmy Fauzy Ahmad (Islamic Economics Journal, 2021)
This paper reviews the evidence of the impact of Islamic microfinance on poverty alleviation and identifies the determinants that can influence microfinance borrowers to realize the SDGs 2030 through a literature review. This study also promotes Islamic microfinance and suggests it as one of the best poverty alleviation tools, especially among Muslim communities by reviewing some of the measures suggested by other researchers through systematic literature reviews. This paper is a literature survey of more than 40 articles related to microfinance that attempt to review and analyze the areas researched by researchers in microfinance. This survey consists not only of empirical analysis and comparative analysis but recommendations and suggestions with some theoretical work. So to achieve the SDGs 2030 goal, it would be very good if Islamic microfinance institutions were used as the main alternative tool to alleviate poverty. Because the program and implementation of Islamic microfinance are always based on maslahah for the community.